Selbstinszenierungspraktiken als Weg zu Stärkenorientierung, Selbstbestimmung und Teilhabe – eine Kollegiale Weiterbildung für multiprofessionelle Akteursgruppen im (inklusiven) Übergang Schule-Beruf - Kundisch, Heike; Kremer, H.-Hugo; Otto, Franziska (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)
Der Beitrag stellt ein Qualifizierungsformat für (multi)professionelle Bildungsakteur*innen zur entwicklungsförderlichen Nutzung von Selbstinszenierungspraktiken vor. Die Konzeption und Entwicklung des Weiterbildungsformats ist im Rahmen eines Forschungs- und Entwicklungsprojekts für Jugendliche in ausbildungsvorbereitenden Bildungsgängen angesiedelt, die einen besonderen Förderbedarf im Zuge des Übergangs von der Schule in die Berufs- und Arbeitswelt aufweisen. Diese sollen durch offene und kreative Selbstdarstellungs- und Erhebungsformate dabei unterstützt werden, ihre Stärken zu erkennen, zu dokumentieren und sichtbar zu machen, sowie hierüber gleichsam für den Übergang Schule-Beruf gestärkt werden. Wir stellen zunächst den Projektrahmen vor und schärfen in diesem Kontext den Zugang über eine Grundlegung zu Selbstinszenierung sowie deren Potenziale im Kontext der inklusiven Berufsbildung und zur Stärkung der Zielgruppe. Das im Projekt entwickelte Rahmenkonzept bietet eine Orientierung zur standort- respektive bildungsgangbezogenen Anpassung und stellt damit Herausforderungen und einen entsprechenden Qualifizierungsbedarf für Bildungsakteur*innen heraus. Darauf basierend stellen wir die konzeptionellen Grundlagen, die methodische und inhaltliche Ausgestaltung zum Ansatz der ‚Kollegialen Weiterbildung‘ zur entwicklungsförderlichen Nutzung von Selbstinszenierungspraktiken vor und adressieren u. a. das Zusammenspiel von innovativer Entwicklung, Schärfung von Rollen und Kompetenzentwicklung der Bildungsakteur*innen. Abschließend diskutieren wir die konzeptionellen Entwicklungen und den Implementations- und Transferansatz. Abstract The article presents a qualification format for multi-professional actors in the educational context on the developmental use of 'Selbstinszenierungspraktiken' (which means a combination of practices for self-awareness, self-realisation and self-acceptance in a process which we are developing in our project). The concept and development of the further education format is located within the framework of a research and development project for young people with wide-ranging needs in pre-vocational education units at the transition from school to work. They will be supported in recognizing, documenting and showing their strengths through open and creative self-expression and survey formats, as well as being strengthened for the transition from school to work. First, we present the project framework and clarify the approach by a theoretical grounding of ‚Selbstinszenierung‘ (similar to a combination of self-awareness, self-realisation and self-acceptance) as well as its potentials in the context of inclusive vocational education by strengthening the target group. The developed framework provides a basis for the adaptation of the concept to a specific location or educational programme and highlights challenges and qualification needs for actors in the educational context. We present the conceptual basis, the methodological and content-related design of the collegial training approach on the developmental use of 'Selbstinszenierungspraktiken'. We address the interaction of innovative development, clarification of roles and competence development of actors in the educational context. Finally, we discuss the conceptual developments and the implementation and transfer approach.
Keywords: General Medicine

Jahrgangsteams zur Kooperation mit Eltern anregen – eine Aufgabe für Fortbildungen? Evaluationsergebnisse zum Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen (BiFoKi) - Grüter, Sandra; Gorges, Julia; Lütje-Klose, Birgit; Neumann, Phillip; Wild, Elke (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)
Für eine gelingende Umsetzung schulischer Inklusion gilt eine professionelle Weiterbildung der Lehrkräfte und des weiteren Schulpersonals als unverzichtbare Voraussetzung, um eine effektive Teamarbeit sowie die Einbindung von Eltern[i] in Erziehungs- und Bildungsprozesse zu gewährleisten. Im Projekt BiFoKi[ii] (Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen) wurde eine Fortbildungsmaßnahme für inklusive Schulen entwickelt, die sowohl die intrainstitutionelle Kooperation innerhalb der Schule als auch die interinstitutionelle Zusammenarbeit mit den Eltern der Schüler*innen mit und ohne sonderpädagogischen Unterstützungsbedarf adressiert. Die Fortbildung zielt u.a. darauf ab, durch eine im Jahrgangsteam gemeinsam geplante und verantwortete Elternarbeit eine einladende Atmosphäre zu schaffen, Kommunikationswege an diverser werdende Bedarfe der Eltern und der Schüler*innen anzupassen und Eltern stärker in schulische Bildungsprozesse einzubeziehen. Zur Evaluation der Fortbildung wurde eine quasi-experimentelle Studie mit einem Prä-Post-Kontrollgruppendesign realisiert. Längsschnittliche Daten liegen für 55 Lehr- und Fachkräfte vor. Die Ergebnisse der varianzanalytischen Auswertung zeigen, dass sich die Einschätzungen zur Kooperationsbereitschaft der Eltern sowie das selbstberichtete Kooperationsverhalten im Bereich der Erziehungs- und Bildungskooperation in der Interventionsgruppe nach der Teilnahme an der Fortbildung signifikant positiver entwickelt hat als in der Kontrollgruppe. [i] Mit dem Begriff Eltern sind hier alle erziehungs- bzw. sorgeberechtigten Personen gemeint. [ii] Hinweis zur Finanzierung: Das diesem Beitrag zugrunde liegende Vorhaben BiFoKi (Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen) wurde mit Mitteln des Bundesministeriums für Bildung und Forschung unter dem Förderkennzeichen 01NV1732in der Förderlinie „Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung“ gefördert (Projektleitung: Birgit Lütje-Klose, Elke Wild, Julia Gorges und Phillip Neumann). Abstract To implement inclusive education successfully, it is crucial that teachers and other school staff are trained to cooperate effectively as a team and to involve parents in educational processes. In the project BiFoKi (Bielefeld Training on Cooperation in inclusive), we developed an in-service training for inclusive schools that addresses the intra-institutional cooperation within schools and the inter-institutional cooperation with the parents of students with and without special educational needs. The training aims to prepare grade-level teams to create a welcoming atmosphere, adapt communication ways to the diverse needs of parents and students and to involve parents more strongly in school educational processes. To evaluate the effectiveness of the training, a quasi-experimental study with a pre-post control group design was implemented. Longitudinal data is available for 55 teachers and other professionals. The results indicate that the intervention group demonstrated a more positive development in terms of satisfaction with parents' willingness to cooperate as well as self-reported cooperative behavior in the area of educational cooperation, compared to the control group.
Keywords: General Medicine

Boron‐Centered Lewis Superacid through Redox‐Active Ligands: Application in C−F and S−F Bond Activation - Köring, Laura; Stepen, Arne; Birenheide, Bernhard; Barth, Simon; Leskov, Maxim; Schoch, Roland; Krämer, Felix; Breher, Frank; Paradies, Jan (Angewandte Chemie)
Keywords: General Medicine

Possible points of blow-up in chemotaxis systems with spatially heterogeneous logistic source - Black, Tobias; Fuest, Mario; Lankeit, Johannes; Mizukami, Masaaki (Nonlinear Analysis: Real World Applications)
Keywords: Applied Mathematics; Computational Mathematics; General Economics; Econometrics and Finance; General Engineering; General Medicine; Analysis

Nanoparticle‐Based Formulations of Glycopeptide Antibiotics: A Means for Overcoming Vancomycin Resistance in Bacterial Pathogens? - Pothineni, Bhanu Kiran; Keller, Adrian (Advanced NanoBiomed Research)
Keywords: General Medicine

Structure–Reactivity Relationships in Borane-Based FLP-Catalyzed Hydrogenations, Dehydrogenations, and Cycloisomerizations - Paradies, Jan (Accounts of Chemical Research)
Keywords: General Medicine; General Chemistry

Effect of a controlled lifestyle intervention on medication use and costs: The Healthy Lifestyle Community Program (cohort 2) - Kranz, Ragna-Marie; Kettler, Carmen; Anand, Corinna; Koeder, Christian; Husain, Sarah; Schoch, Nora; Buyken, Anette; Englert, Heike (Nutrition and Health)
Background: Establishing a healthy lifestyle has a great potential to reduce the prevalence of non-communicable diseases (NCDs) and their risk factors. NCDs contribute immensely to the economic costs of the health care system arising from therapy, medication use, and productivity loss. Aim: The aim of this study was to evaluate the effect of the Healthy Lifestyle Community Program (cohort 2; HLCP-2) on medication use and consequently on medication costs for selected NCDs (diabetes, hypertension, and dyslipidemia). Methods: Data stem from a 24-month non-randomised, controlled intervention trial aiming to improve risk factors for NCDs. Participants completed questionnaires at six measurement time points assessing medication use, from which costs were calculated. The following medication groups were included in the analysis as NCD medication: glucose-lowering medications (GLM), antihypertensive drugs (AHD) and lipid-lowering drugs (LLD). Statistical tests for inter- and intra-group comparison and multiple regression analysis were performed. Results: In total, 118 participants (intervention group [IG]: n = 79; control group [CG]: n = 39) were considered. Compared to baseline medication use decreased slightly in the IG and increased in the CG. Costs for NCD medication were significantly lower in the IG than in the CG after 6 ( p = 0.004), 12 ( p = 0.040), 18 ( p = 0.003) and 24 months ( p = 0.008). After multiple regression analysis and adjusting for confounders, change of costs differed significantly between the groups in all final models. Conclusion: The HLCP-2 was able to moderately prevent an increase of medication use and thus reduce costs for medication to treat NCDs with the greatest impact on AHD. Trial registration German Clinical Trials Register DRKS ( www.drks.de ; reference: DRKS00018775).
Keywords: Nutrition and Dietetics; General Medicine; Medicine (miscellaneous)

Geschlechterspezifische Effekte in der bewegungstherapeutischen Behandlung von hämodynamischen Regulationsstörungen bei Morbus Parkinson - Siche-Pantel, Franziska; Jakobsmeyer, Rasmus; Buschfort, Rüdiger; Mühlenberg, Manfred; Michels, Heinke; Oesterschlink, Julian; Reinsberger, Claus (B&G Bewegungstherapie und Gesundheitssport)
Zusammenfassung Einleitung Motorische Symptome bei Morbus Parkinson lassen sich durch körperliche Aktivität modifizieren. Inwiefern dies auch für nicht-motorische, autonome Symptome gilt, ist weitaus weniger bekannt. Die Erkrankung weist zudem eine Vielzahl an geschlechterspezifischen Unterschieden auf. Epidemiologische Untersuchungen deuten zum Beispiel auf einen besseren primärpräventiven Effekt durch körperliche Aktivität bei Männern als bei Frauen hin. Daten zu geschlechterspezifischen Effekten auf das autonome Nervensystem sind jedoch limitiert. Im Rahmen der vorliegenden Pilotstudie sollen mögliche geschlechterspezifische Effekte einer Bewegungsintervention auf Störungen der hämodynamischen Regulation als Manifestation nicht-motorischer Symptome untersucht werden. Diese sind aufgrund ihrer oft gegensätzlichen hypo- und hypertonen Ausprägung schwierig medikamentös zu behandeln, lassen sich aber gegebenenfalls durch Bewegungsinterventionen modifizieren. Methodik Bei 42 Patienten und Patientinnen (Alter: 70,3 Jahre; 24 Männer; 18 Frauen) wurden vor und nach einer mehrwöchigen, stationären Parkinsonkomplexbehandlung hämodynamische Parameter in einem Schellongtest untersucht. Mittels anschließender Regressionsanalyse erfolgte eine Quantifizierung der Abhängigkeit von den Faktoren Alter, Body Mass Index, Krankheitsdauer, Vorerkrankungen, Sitzendblutdruck und hypotensiv wirkender Medikamente. Ergebnis Bei 44% der Männer und 46% der Frauen traten hämodynamische Regulationsstörungen im Stand und in Rückenlage mindestens einmal auf. Eine vor Therapiebeginn präsentierte Regulationsstörung im Stand zeigte sich in keiner Geschlechtergruppe durch die Parkinsonkomplexbehandlung verändert. Frauen zeigten zu Therapieende jedoch einen signifikant niedrigeren Blutdruck im Liegen (p=0,022*). Unabhängig von der Komplextherapie fiel der Blutdruck in Rückenlage bei Frauen nach Orthostasebelastung höher aus als davor (vor Therapie: p=0,015 *; nach Therapie: p=0,021*). Jedes Lebensjahr erhöhte das Risiko für eine hämodynamische Regulationsstörung in Rückenlage in der Gesamtgruppe um 12,4% (Regressionskoeffizient B=0,117; p=0,014 *; Exp(B)=1,124). Schlussfolgerung Systematische Effekte auf Blutdruckwerte im Rahmen von Orthostasereaktionen durch eine Parkinsonkomplexbehandlung konnten nicht nachgewiesen werden. Allerdings zeigte sich bei Frauen nach Parkinsonkomplexbehandlung eine Senkung der Blutdruckwerte in Rückenlage. Das scheinbar unsystematische, teils geschlechterspezifische Auftreten hämodynamischer Regulationsstörungen fordert ein individualmedizinisch angelegtes Vorgehen im therapeutischen Alltag.
Keywords: General Medicine

Adsorption of Ferritin at Nanofaceted Al2O3 Surfaces - Pothineni, Bhanu K.; Kollmann, Sabrina; Li, Xinyang; Grundmeier, Guido; Erb, Denise J.; Keller, Adrian (International Journal of Molecular Sciences)
The influence of nanoscale surface topography on protein adsorption is highly important for numerous applications in medicine and technology. Herein, ferritin adsorption at flat and nanofaceted, single-crystalline Al2O3 surfaces is investigated using atomic force microscopy and X-ray photoelectron spectroscopy. The nanofaceted surfaces are generated by the thermal annealing of Al2O3 wafers at temperatures above 1000 °C, which leads to the formation of faceted saw-tooth-like surface topographies with periodicities of about 160 nm and amplitudes of about 15 nm. Ferritin adsorption at these nanofaceted surfaces is notably suppressed compared to the flat surface at a concentration of 10 mg/mL, which is attributed to lower adsorption affinities of the newly formed facets. Consequently, adsorption is restricted mostly to the pattern grooves, where the proteins can maximize their contact area with the surface. However, this effect depends on the protein concentration, with an inverse trend being observed at 30 mg/mL. Furthermore, different ferritin adsorption behavior is observed at topographically similar nanofacet patterns fabricated at different annealing temperatures and attributed to different step and kink densities. These results demonstrate that while protein adsorption at solid surfaces can be notably affected by nanofacet patterns, fine-tuning protein adsorption in this way requires the precise control of facet properties.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

How to Speak Silently — Rethinking Materiality, Agency, and Communicative Competence in Virtual Reality - A. Erofeeva, Maria; Klowait, Nils; Zababurin, Denis (Sociology of Power)
Keywords: General Medicine

Producing deceptive actions in sports: The costs of generating head fakes in basketball - Güldenpenning, Iris; Weigelt, Matthias; Böer, Nils Tobias; Kunde, Wilfried (Human Movement Science)
Typically, head fakes in basketball are generated to, and actually do, deteriorate performance on the side of the observer. However, potential costs at the side of the producer of a fake action have only rarely been investigated before. It is thus not clear yet if the benefit (i.e., slowed reactions in the observer) of performing a head fake is overestimated due to concurrently arising fake production costs (i.e., slowed performance in the producer of a head fake). Therefore, we studied potential head-fake production costs with two experiments. Novice participants were asked to generate passes to the left or right side, either with or without head fakes. In Experiment 1, these actions were determined by an auditory stimulus (i.e., a 440 Hz or 1200 Hz sinus or jigsaw wave). After an interstimulus interval (ISI) of either 0 ms, 800 ms, or 1500 ms, which served the preparation of the action, the cued action had to be executed. In Experiment 2, passing to the left or right, either with or without a head fake, was determined by a visual stimulus (i.e., a player with a red or blue jersey defending either the right or left side). After an ISI of either 0 ms, 400 ms, 800 ms, or 1200 ms, the cued action had to be executed. In both experiments, we observed higher reaction times (RTs) for passes with head fakes as compared to passes without head fakes for no and an intermediate preparation interval (from ISI 0 ms to 800 ms), but no difference for a long preparation interval (for an ISI of 1200 ms and 1500 ms). Both experiments show that generating fake actions produces performance costs, however, these costs can be overcome by a longer preparation phase before movement execution.
Keywords: Experimental and Cognitive Psychology; Orthopedics and Sports Medicine; General Medicine; Biophysics

Die Doppelwirkung von Information für klimafreundliches Handeln - Frick, Marc; Foese, Dario; Von Graevenitz, Kathrine; Kesternich, Martin; Wagner, Ulrich
Informationen sind für eine erfolgreiche Klimapolitik in doppelter Hinsicht wichtig: Sie werden benötigt, wenn Potenziale zur Vermeidung von Emissionen identifiziert und klimapolitische Instrumente ausgewählt werden. Und sie sind zentral, damit Bürger/innen selbst Entscheidungen im Sinne des Klimaschutzes treffen können.
Keywords: General Medicine

An Integrative View of the Transformations towards Sustainability and Digitalization: The Case for a Dual Transformation - Kürpick, Christian; Rasor, Anja; Scholtysik, Michel; Kühn, Arno; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Identification and prediction of standard times in machining for precision steel tubes through the usage of data analytics - Weller, Julian; Roesmann, Daniel; Eggert, Sönke; von Enzberg, Sebastian; Gräßler, Iris; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Design of individual simulation games in manufacturing companies for game-based learning - Machon, Fabian; Gabriel, Stefan; Latos, Benedikt; Holtkötter, Christoph; Lütkehoff, Ben; Asmar, Laban; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Process Mining Data Canvas: A method to identify data and process knowledge for data collection and preparation in process mining projects - Brock, Jonathan; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Targeted-oriented selection of engineering methods - Wilke, Daria; Schierbaum, Anja; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Stakeholder-oriented Elaboration of Artificial Intelligence use cases using the example of Special-Purpose engineering - Humpert, Lynn; Wäschle, Moritz; Horstmeyer, Sarah; Anacker, Harald; Dumitrescu, Roman; Albers, Albert (Procedia CIRP)
Keywords: General Medicine

'Surprised, Shocked, Worried'}: User Reactions to Facebook Data Collection from Third Parties - Arias-Cabarcos, Patricia; Khalili, Saina; Strufe, Thorsten (Proceedings on Privacy Enhancing Technologies)
Data collection and aggregation by online services happens to an extent that is often beyond awareness and comprehension of its users. Transparency tools become crucial to inform people, though it is unclear how well they work. To investigate this matter, we conducted a user study focusing on Facebook, which has recently released the 'Off-Facebook Activity' transparency dashboard that informs about personal data collection from third parties. We exposed a group of n = 100 participants to the dashboard and surveyed their level of awareness and reactions to understand how transparency impacts users' privacy attitudes and intended behavior. Our participants were surprised about the massive amount of collected data, became significantly less comfortable with data collection, and more likely to take protective measures. Collaterally, we observed that current consent schemes are inadequate. Based on the survey findings, we make recommendations for more usable transparency and highlight the need to raise awareness about transparency tools and to provide easily actionable privacy controls.
Keywords: General Medicine

Imagine to automatize: automatization of stimulus–response coupling after action imagery practice in implicit sequence learning - Dahm, Stephan F.; Hyna, Henri; Krause, Daniel (Psychological Research)
Abstract Action imagery practice (AIP) describes the repetitive imagination of an action to improve subsequent action execution. Because AIP and action execution practice (AEP) draw on partly similar motor mechanisms, it was assumed that AIP may lead to motor automatization, which is observable in a reduction of dual-task costs after AEP. To investigate automatization in AIP, we compared dual-task and single-task performance in practice and random sequences in pretests and posttests. All participants practiced serial reactions to visual stimuli in ten single-task practice sessions. An AIP group imagined the reactions. An AEP group and a control practice group executed the reactions. Practice followed a sequential sequence in AIP and AEP but was random in control practice. In dual-task test conditions, tones were counted that appeared in addition to the visual stimuli. RTs decreased from pretest to posttest in both practice and random sequences in all groups indicating general sequence-unspecific learning. Further, RTs decreased to a greater extent in the practice sequence than in the random sequence after AIP and AEP, indicating sequence-specific learning. Dual-task costs—the difference between RTs after tone and no tone events—were reduced independent from the performed sequence in all groups indicating sequence-unspecific automatization. It is concluded that the stimulus–response coupling can be automatized by both, AEP and AIP.
Keywords: Arts and Humanities (miscellaneous); Developmental and Educational Psychology; Experimental and Cognitive Psychology; General Medicine

A systematic literature review on the Digital Twin of the factory in the context of the product and factory lifecycle - Cieply, Jonas; Disselkamp, Jan-Philipp; Dyck, Florian; Alturk, Waddah; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Development of a modular architecture for complex mechatronic systems - Seidenberg, Tobias; Disselkamp, Jan-Philipp; Jürgenhake, Christoph; Grobbel, Daniel; Dumitrescu, Roman; Papanikolaou, Apostolos (Procedia CIRP)
Keywords: General Medicine

Integrated product and production development - a systematic literature review - Disselkamp, Jan-Philipp; Cieply, Jonas; Dyck, Florian; Grothe, Robin; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Systematics for an Integrative Modelling of Product and Production System - Schäfer, Louis; Günther, Matthias; Martin, Alex; Lüpfert, Mariella; Mandel, Constantin; Rapp, Simon; Lanza, Gisela; Anacker, Harald; Albers, Albert; Köchling, Daniel (Procedia CIRP)
Keywords: General Medicine

Virtual Assembly for Engineering – A Systematic Literature Review - Dyck, Florian; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Practice reduces the costs of producing head fakes in basketball - Böer, Nils Tobias; Weigelt, Matthias; Schütz, Christoph; Güldenpenning, Iris (Psychological Research)
Abstract Previous research indicates that performing passes with a head fake in basketball leads to increased response initiation times and errors as compared to performing a pass without a head fake. These so-called fake production costs only occurred when not given the time to mentally prepare the deceptive movement. In the current study, we investigated if extensive practice could reduce the cognitive costs of producing a pass with head fake. Twenty-four basketball novices participated in an experiment on five consecutive days. A visual cue prompted participants to play a pass with or without a head fake either to the left or right side. The cued action had to be executed after an interstimulus interval (ISI) of either 0 ms, 400 ms, 800 ms or 1200 ms, allowing for different movement preparation times. Results indicated higher response initiation times (ITs) and error rates (ERs) for passes with head fakes for the short preparation intervals (ISI 0 ms and 400 ms) on the first day but no difference for the longer preparation intervals (ISI 800 ms and 1200 ms). After only one day of practice, participants showed reduced fake production costs (for ISI 0 ms) and were even able to eliminate these cognitive costs when given time to mentally prepare the movement (for ISI 400 ms). Accordingly, physical practice can reduce the cognitive costs associated with head-fake generation. This finding is discussed against the background of the strengthening of stimulus response associations.
Keywords: Arts and Humanities (miscellaneous); Developmental and Educational Psychology; Experimental and Cognitive Psychology; General Medicine

Integrative conceptualization of products and business models for the circular economy: A systematic literature review - Scholtysik, Michel; Koldewey, Christian; Rohde, Malte; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Die Doppelwirkung von Information für klimafreundliches Handeln - Frick, Marc; Foese, Dario; Von Graevenitz, Kathrine; Kesternich, Martin; Wagner, Ulrich
Informationen sind für eine erfolgreiche Klimapolitik in doppelter Hinsicht wichtig: Sie werden benötigt, wenn Potenziale zur Vermeidung von Emissionen identifiziert und klimapolitische Instrumente ausgewählt werden. Und sie sind zentral, damit Bürger/innen selbst Entscheidungen im Sinne des Klimaschutzes treffen können.
Keywords: General Medicine

Investigation of the Compatibility between Warheads and Peptidomimetic Sequences of Protease Inhibitors—A Comprehensive Reactivity and Selectivity Study - Müller, Patrick; Meta, Mergim; Meidner, Jan Laurenz; Schwickert, Marvin; Meyr, Jessica; Schwickert, Kevin; Kersten, Christian; Zimmer, Collin; Hammerschmidt, Stefan Josef; Frey, Ariane; Lahu, Albin; de la Hoz-Rodríguez, Sergio; et al. (International Journal of Molecular Sciences)
Covalent peptidomimetic protease inhibitors have gained a lot of attention in drug development in recent years. They are designed to covalently bind the catalytically active amino acids through electrophilic groups called warheads. Covalent inhibition has an advantage in terms of pharmacodynamic properties but can also bear toxicity risks due to non-selective off-target protein binding. Therefore, the right combination of a reactive warhead with a well-suited peptidomimetic sequence is of great importance. Herein, the selectivities of well-known warheads combined with peptidomimetic sequences suited for five different proteases were investigated, highlighting the impact of both structure parts (warhead and peptidomimetic sequence) for affinity and selectivity. Molecular docking gave insights into the predicted binding modes of the inhibitors inside the binding pockets of the different enzymes. Moreover, the warheads were investigated by NMR and LC-MS reactivity assays against serine/threonine and cysteine nucleophile models, as well as by quantum mechanics simulations.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Grundschullehramt zwischen Professionalität und De-Professionalisierung. Herausforderungen der Lehrkräftequalifizierung für eine hochwertige grundlegende Bildung in der Grundschule - Rank, Astrid; Büker, Petra; Miller, Susanne; Martschinke, Sabine (Erziehungswissenschaft)
Keywords: General Medicine

Agentenbasierte Modellierung und Simulation im Pandemiemanagement - Hälterlein, Jens (TATuP - Zeitschrift für Technikfolgenabschätzung in Theorie und Praxis)
Mathematical models and computer simulations play a crucial role in the context of the COVID-19 crisis for knowledge about the possible course of the pandemic and for appropriate policy decisions. The paper presents results from an ethnographic study of a government-funded R & D project dealing with agent-based modeling and simulation (ABMS) in the context of pandemic management. Based on the assumption that the use of computer simulations in pandemic management is not only a means to an end for political or epidemiological goals but also plays a significant role in determining which goals and strategies appear politically legitimate, the paper reconstructs how insights into the pandemic are generated in ABMS and specifically in the researched project and made accessible for decision-making.
Keywords: General Medicine

Adaptive Koopman-Based Models for Holistic Controller and Observer Design - Junker, Annika; Pape, Keno Egon Friedrich; Timmermann, Julia; Trächtler, Ansgar (IFAC-PapersOnLine)
Keywords: General Medicine

Herkunftsbedingte und sprachliche Einflüsse bei der häuslichen Internetnutzung von Kindern - Richter, Lea; Gruchel, Nicole; Buhl, Heike M.; Kamin, Anna-Maria (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)
Der Beitrag betrachtet die digitale häusliche Lernumwelt von Kindern unter besonderer Berücksichtigung der Differenzkategorien Herkunft und Sprache und erarbeitet Zusammenhänge zwischen dem Migrationshintergrund, der Familiensprache, einer internetbezogenen Eltern-Kind-Interaktion sowie einer unterhaltungs- und schulbezogenen Nutzung des Internets von Kindern. Empirische Grundlagen sind standardisierte Eltern- und Kinderbefragungen sowie ethnografisch orientierte Untersuchungen in Familien. Die quantitativen Analysen zeigen, dass Kinder, deren Hauptverkehrssprache in der Familie nicht Deutsch ist, häufiger gemeinsam mit ihren Eltern das Internet nutzten. Vertiefend liessen in der qualitativen Untersuchung diejenigen Kinder häufigere und komplexere Internetnutzungsformen für schulische Zwecke erkennen, die einen Migrationshintergrund aufweisen und hauptsächlich in ihrer Herkunftssprache (nicht Deutsch) innerhalb der Familie sprechen. Insbesondere in Familien, die selten in der Häuslichkeit Deutsch sprechen, hat sich die (gemeinsame) Internetrecherche als Mittel zur Kompensation von Sprachbarrieren erwiesen. Fehlende elterliche Unterstützungsmöglichkeiten aufgrund von sprachlichen Verständnisproblemen können insofern durch kindliche, elterliche oder gemeinsame Rechercheprozesse ausgeglichen werden.
Keywords: General Medicine

Deutsch für den Beruf [Sammelrezension] Sander, Isa-Lou; Efing, Christian (Hrsg.): Der Betrieb als Sprachlernort. Tübingen: Narr Francke Attempto, 2021 (Kommunizieren im Beruf, 4). -- ISBN 978-3-8233-8442-7. 264 Seiten, € 68,00. Tichy, Ellen; Tesch, Felicitas (Hrsg.): Deutsch in Fach und Beruf. Aktuelle Fragen und neue Ansätze der Fremdsprachenvermittlung. Berlin: Peter Lang, 2021 (Berufssprache Deutsch in Theorie und Praxis, 2). -- ISBN 978-3-631-79553-8. 194 Seiten, € 49,95. Niederhaus, Constanze: Deutsch für den Beruf. Eine Einführung. Berlin: Erich Schmidt, 2022 (Grundlagen Deutsch als Fremd- und Zweitsprache, 4). -- ISBN 978-3-503-20545-5. 265 Seiten, € 22,00. - Prikoszovits, Matthias (Informationen Deutsch als Fremdsprache)
Keywords: General Medicine

Nächtliche sympathische Aktivität und subjektive Symptome nach sport-assoziierter Concussion: eine Pilotstudie - Delling, Anne Carina; Jakobsmeyer, Rasmus; Christiansen, Nele; Coenen, Jessica; Reinsberger, Claus (B&G Bewegungstherapie und Gesundheitssport)
Zusammenfassung Einleitung Eine sport-assoziierte Concussion (saC) ist eine oftmals unterschätzte Hirnverletzung, die vor allem in Kontakt- und Kollisionssportarten häufig vorkommt. SaCs können zu einer Vielzahl an klinischen Symptomen führen. Akute und zum Teil die klinische Regeneration überdauernde parasympathische Inhibierung im Autonomen Nervensystem (ANS) wurde nach saC bereits häufig beschrieben. Über Veränderungen im sympathischen Nervensystem ist jedoch noch wenig bekannt. Diese wurden durch Messungen der elektrodermalen Aktivität (EDA) im Schlaf, der erheblich zur Regeneration nach saC beiträgt, sowie im Zusammenhang mit subjektiven Symptomen nach saC im Rahmen einer Pilotstudie untersucht. Methode 18 Sportler und Sportlerinnen mit diagnostizierter saC und 18 nach Alter, Geschlecht, Größe, Gewicht, Sportart und Leistungsklasse gematchte Kontrollathleten und -athletinnen trugen in den Nächten während der individuellen Return-to-Sport (RTS) Phase sowie drei Wochen nach Abschluss des RTS (postRTS) einen Handgelenkssensor (E4 Empatica Inc., Mailand, Italien). Anteile nächtlicher tonischer (meanEDA) und phasischer (EDRs, Schlafstürme) EDA wurden zwecks Gruppenvergleich ermittelt und mit saC-Symptomen (SCAT5) sowie dem subjektiven Erholungszustand nach Schlaf mittels Mann-Whitney U-Tests oder ungepaarten t-Tests verglichen. Ergebnisse Während und nach dem RTS konnten keine Gruppenunterschiede in den nächtlichen EDA-Parametern nachgewiesen werden. Eine höhere meanEDA während des RTS korrelierte mit einer höheren Anzahl an Symptomen (p=0,025, r=0,525) und eine erhöhte phasische EDA mit einem geringeren Anstieg des subjektiven Erholungszustands von vor zu nach Schlaf (EDRs: p=0,007, r=−0,642; EDRs/min: p>0,001, r=−0,762; Schlafstürme: p=0,011, r=−0,616). Fazit Die nächtliche EDA nach saC unterschied sich während und nach dem RTS nicht signifikant zu gematchten Kontrollsportlern und -sportlerinnen. Der Zusammenhang zwischen höherer EDA während des RTS und der Anzahl an saC-Symptomen sowie der geringeren subjektiven Erholung nach Schlaf könnte sowohl ursächlich für als auch Effekt der subjektiven Symptome sein und sollte durch Baseline-Messungen und in Kombination mit parasympathischen Markern künftig weiter untersucht werden.
Keywords: General Medicine

Digitalisiertes Arbeiten in gastgewerblichen Berufen – Umsetzung in der Hochschullehre - Härtel, Sandra; Klatt, Christiane; Meyer, Anja (HiBiFo – Haushalt in Bildung & Forschung)
In einem Seminar für angehende berufsbildende Lehrkräfte der beruflichen Fachrichtung Ernährung und Hauswirtschaft an der Technischen Universität Dresden wurde mittels digitaler Tools ein Property-Management-System dargestellt. Ziel ist es, Geschäfts- und Arbeitsprozesse in der Hotellerie sowie digitale Medien und ihre Einsatzmöglichkeiten innerhalb von Lehrveranstaltungen abzubilden.
Keywords: General Medicine

Halting the Decay of Talk - Klowait, Nils; Erofeeva, Maria (Social Interaction. Video-Based Studies of Human Sociality)
We investigate how people with atypical bodily capabilities interact within virtual reality (VR) and the way they overcome interactional challenges in these emerging social environments. Based on a videographic multimodal single case analysis, we demonstrate how non-speaking VR participants furnish their bodies, at-hand instruments, and their interactive environment for their practical purposes. Our findings are subsequently related to renewed discussions of the relationship between agency and environment, and the co-constructed nature of situated action. We thus aim to contribute to the growing vocabulary of atypical interaction analysis and the broader context of ethnomethodological conceptualizations of unorthodox and fractured interactional ecologies.
Keywords: General Medicine

Identification and prediction of standard times in machining for precision steel tubes through the usage of data analytics - Weller, Julian; Roesmann, Daniel; Eggert, Sönke; von Enzberg, Sebastian; Gräßler, Iris; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Analysis of a chemotaxis-SIS epidemic model with unbounded infection force - Tao, Youshan; Winkler, Michael (Nonlinear Analysis: Real World Applications)
Keywords: Applied Mathematics; Computational Mathematics; General Economics; Econometrics and Finance; General Engineering; General Medicine; Analysis

A bi-objective hybrid vibration damping optimization model for synchronous flow shop scheduling problems - Tavana, Madjid; Hajipour, Vahid; Alaghebandha, Mohammad; Di Caprio, Debora (Machine Learning with Applications)
Keywords: General Medicine

A comparative performance analysis of intelligence-based algorithms for optimizing competitive facility location problems - Hajipour, Vahid; Niaki, Seyed Taghi Akhavan; Tavana, Madjid; Santos-Arteaga, Francisco J.; Hosseinzadeh, Sanaz (Machine Learning with Applications)
Keywords: General Medicine

‹Ich sehe was, was du nicht siehst…› Zu den Potenzialen von Sketchnoting im Kontext Inklusiver Medienbildung - Kückmann, Marie-Ann (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)
Wiederholt wird im Inklusionszusammenhang auf die Bedeutung von Medien verwiesen. Inklusion und Mediatisierung werden dabei als relevante, grundlegende gesellschaftliche Transformationen zunehmend zusammen gedacht. So wird im Kontext des Diskurses um inklusive Medienbildung immer wieder darauf hingewiesen, dass Medien eben Möglichkeiten zur Teilhabe und Interaktion bedingen und darüber entsprechend Kultur d. h. zugrundeliegende Inhalte, Werte usw. (mit) herstellen. Ausgehend von diesen Grundgedanken soll vorliegend neben Inklusion und Mediatisierung auch eine zunehmende Visualisierung als untrennbar miteinander verbundene Prozesse vor dem Hintergrund transformatorischer Bildung in den Blick genommen werden. So ist nicht zuletzt im Zuge digitaler Transformation festzustellen, dass visuelle Ausdrucksformen resp. neuere Kommunikationsmedien wie bspw. «Sketchnotes» vermehrt Eingang in unterschiedliche Lebensbereiche finden. So erfreuen sich etwa Ansätze wie «Graphic Recording» sowie «Visual Facilitation» sowohl im betrieblichen Kontext als auch im (Weiter-)Bildungsbereich zunehmender Beliebtheit. Dabei sind im Besonderen Fragen danach, was das Prinzip Sketchnoting als spezifische mediale Artikulation überhaupt ausmacht und inwiefern dieses hierauf aufbauend einen Beitrag zur inklusiven Medienbildung leisten kann, jedoch weitgehend ungeklärt. Der vorliegende Artikel widmet sich diesen und ähnlichen Fragestellungen aus theoretischer Perspektive, kennzeichnet Sketchnoting als grundlegenden dynamisch-dialektischen Prozess (also bspw. als Wechselspiel von Simultaneität und Sukzession, von Emotionsförderung und Versachlichung sowie von Abstrahierung und Konkretisierung), leitet aufbauend neuartige mediale Ausdrucks-, Interaktions- resp. Verständigungsmöglichkeiten ab und soll so auch einen Ausgangspunkt für weitere Diskussionen sowie für die empirische Forschung eröffnen.
Keywords: General Medicine

Scenario-based Foresight in the Age of Digitalization and Artificial Intelligence – Identification and Analysis of Existing Use Cases - Ködding, Patrick; Ellermann, Kai; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Salting-Out of DNA Origami Nanostructures by Ammonium Sulfate - Hanke, Marcel; Hansen, Niklas; Chen, Ruiping; Grundmeier, Guido; Fahmy, Karim; Keller, Adrian (International Journal of Molecular Sciences)
DNA origami technology enables the folding of DNA strands into complex nanoscale shapes whose properties and interactions with molecular species often deviate significantly from that of genomic DNA. Here, we investigate the salting-out of different DNA origami shapes by the kosmotropic salt ammonium sulfate that is routinely employed in protein precipitation. We find that centrifugation in the presence of 3 M ammonium sulfate results in notable precipitation of DNA origami nanostructures but not of double-stranded genomic DNA. The precipitated DNA origami nanostructures can be resuspended in ammonium sulfate-free buffer without apparent formation of aggregates or loss of structural integrity. Even though quasi-1D six-helix bundle DNA origami are slightly less susceptible toward salting-out than more compact DNA origami triangles and 24-helix bundles, precipitation and recovery yields appear to be mostly independent of DNA origami shape and superstructure. Exploiting the specificity of ammonium sulfate salting-out for DNA origami nanostructures, we further apply this method to separate DNA origami triangles from genomic DNA fragments in a complex mixture. Our results thus demonstrate the possibility of concentrating and purifying DNA origami nanostructures by ammonium sulfate-induced salting-out.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Time-Dependent DNA Origami Denaturation by Guanidinium Chloride, Guanidinium Sulfate, and Guanidinium Thiocyanate - Hanke, Marcel; Hansen, Niklas; Tomm, Emilia; Grundmeier, Guido; Keller, Adrian (International Journal of Molecular Sciences)
Guanidinium (Gdm) undergoes interactions with both hydrophilic and hydrophobic groups and, thus, is a highly potent denaturant of biomolecular structure. However, our molecular understanding of the interaction of Gdm with proteins and DNA is still rather limited. Here, we investigated the denaturation of DNA origami nanostructures by three Gdm salts, i.e., guanidinium chloride (GdmCl), guanidinium sulfate (Gdm2SO4), and guanidinium thiocyanate (GdmSCN), at different temperatures and in dependence of incubation time. Using DNA origami nanostructures as sensors that translate small molecular transitions into nanostructural changes, the denaturing effects of the Gdm salts were directly visualized by atomic force microscopy. GdmSCN was the most potent DNA denaturant, which caused complete DNA origami denaturation at 50 °C already at a concentration of 2 M. Under such harsh conditions, denaturation occurred within the first 15 min of Gdm exposure, whereas much slower kinetics were observed for the more weakly denaturing salt Gdm2SO4 at 25 °C. Lastly, we observed a novel non-monotonous temperature dependence of DNA origami denaturation in Gdm2SO4 with the fraction of intact nanostructures having an intermediate minimum at about 40 °C. Our results, thus, provide further insights into the highly complex Gdm–DNA interaction and underscore the importance of the counteranion species.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Psychological readiness of elite rugby players at return to play after severe knee injury - Robyn, A.D.; Louw, Q.A.; Baumeister, Jochen (African Journal for Physical Activity and Health Sciences (AJPHES))
Keywords: General Medicine

Using vibration data to classify conditions in disk stack separators - Merkelbach, Silke; Afroze, Lameya; Janssen, Nils; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (Vibroengineering PROCEDIA)
Mounting sensors in disk stack separators is often a major challenge due to the operating conditions. However, a process cannot be optimally monitored without sensors. Virtual sensors can be a solution to calculate the sought parameters from measurable values. We measured the vibrations of disk stack separators and applied machine learning (ML) to detect whether the separator contains only water or whether particles are also present. We combined seven ML classification algorithms with three feature engineering strategies and evaluated our model successfully on vibration data of an experimental disk stack separator. Our experimental results demonstrate that random forest in combination with manual feature engineering using domain specific knowledge about suitable features outperforms all other models with an accuracy of 91.27 %.
Keywords: General Medicine

Comparing lab and field agility kinematics in young talented female football players: Implications for ACL injury prevention - Di Paolo, Stefano; Nijmeijer, Eline; Bragonzoni, Laura; Dingshoff, Evelien; Gokeler, Alli; Benjaminse, Anne (European Journal of Sport Science)
Keywords: Orthopedics and Sports Medicine; Physical Therapy; Sports Therapy and Rehabilitation; General Medicine

Comparing lab and field agility kinematics in young talented female football players: Implications for ACL injury prevention - Di Paolo, Stefano; Nijmeijer, Eline; Bragonzoni, Laura; Dingshoff, Evelien; Gokeler, Alli; Benjaminse, Anne (European Journal of Sport Science)
Keywords: Orthopedics and Sports Medicine; Physical Therapy; Sports Therapy and Rehabilitation; General Medicine

High‐Resolution Study of Changes in Morphology and Chemistry of Cylindrical PS‐ b ‐PMMA Block Copolymer Nanomasks during Mask Development - Bürger, Julius; Venugopal, Harikrishnan; Kool, Daniel; de los Arcos, Teresa; Gonzalez Orive, Alejandro; Grundmeier, Guido; Brassat, Katharina; Lindner, Jörg K.N. (Advanced Materials Interfaces)
Keywords: General Medicine